Economic Competitiveness in the Global Vegetables Value Chain – A Factor Influencing Food Security and the Production–Consumption–Trade Balance Nexus in Romania - Marius CONSTANTIN; Vlad Constantin TURCEA; Iuliana Denisa RADULESCU (Communications of International Proceedings, 2021)
Economic competitiveness in the global agri-food value chain is one the vectors that significantly impact food production patterns and other aspects related to food security and the international agri-food trade. Consumption behaviors and foreign trade are also influenced by the specific demands expressed at global scale. In the race for achieving better economic results through the lens of key performance indicators, food security issues might arise as a result of chronic import dependencies emergence in particular types of agri-food products. Taking this into consideration, the main objective of this research was to tap into the nature of economic competitiveness in the global vegetables value chain and to explore its implications in achieving food security and concerning the production–consumption–trade balance nexus in Romania. Results show an exacerbated rhythm of vegetables’ imports, far greater than exports, especially tomatoes and potatoes, despite Romania’s agricultural potential. The average consumption of potatoes decreased and so did the production over the last years in Romania, but the trade balance registered a deficit peak in 2019. However, tomatoes are net contributors in the negative trade balance results as far as the vegetables class is concerned. Overcoming this unfavorable situation for Romania implies decision makers to fully understand farmers’ needs and to ensure that enough support is offered in order to successfully elaborate and implement investment projects in the agri-food sector.
Keywords: Global Agri-Food Value Chain; Value Creation; Foreign Trade; Market Patterns.